Prevalence and course of disease after lung resection in primary ciliary dyskinesia: a cohort & nested case-control study - KARADAĞ, BÜLENT TANER (BMC, 2019)
Background Lung resection is a controversial and understudied therapeutic modality in Primary Ciliary Dyskinesia (PCD). We assessed the prevalence of lung resection in PCD across countries and compared disease course in lobectomised and non-lobectomised patients. Methods In the international iPCD cohort, we identified lobectomised and non-lobectomised age and sex-matched PCD patients and compared their characteristics, lung function and BMI cross-sectionally and longitudinally. Results Among 2896 patients in the iPCD cohort, 163 from 20 centers (15 countries) underwent lung resection (5.6%). Among adult patients, prevalence of lung resection was 8.9%, demonstrating wide variation among countries. Compared to the rest of the iPCD cohort, lobectomised patients were more often females, older at diagnosis, and more often had situs solitus. In about half of the cases (45.6%) lung resection was performed before presentation to specialized PCD centers for diagnostic work-up. Compared to controls (n = 197), lobectomised patients had lower FVC z-scores (- 2.41 vs - 1.35, p = 0.0001) and FEV1 z-scores (- 2.79 vs - 1.99, p = 0.003) at their first post-lung resection assessment. After surgery, lung function continued to decline at a faster rate in lobectomised patients compared to controls (FVC z-score slope: - 0.037/year Vs - 0.009/year, p = 0.047 and FEV1 z-score slope: - 0.052/year Vs - 0.033/year, p = 0.235), although difference did not reach statistical significance for FEV1. Within cases, females and patients with multiple lobe resections had lower lung function. Conclusions Prevalence of lung resection in PCD varies widely between countries, is often performed before PCD diagnosis and overall is more frequent in patients with delayed diagnosis. After lung resection, compared to controls most lobectomised patients have poorer and continuing decline of lung function despite lung resection. Further studies benefiting from prospective data collection are needed to confirm these findings.
Keywords: Kartagener syndrome (MeSH); Ciliary motility disorders (MeSH); Lobectomy; CYSTIC-FIBROSIS PATIENTS; MIDDLE LOBE SYNDROME; CHILDREN; MANAGEMENT; DIAGNOSIS; FEATURES